Transformations of Modern Gastronomic Culture and the Totality of Fast Food - Irina Sokhan (Journal of Economic Sociology, 2013)
The paper presents a short description of the research project carried out within The National Research University Higher School of Economics’ Academic Fund Program in January 15, 2013 — May 15, 2014. In the modern world, traditional gastronomic practices and gastronomic culture undergo dramatic transformations. Their role in the formation of human identity is becoming more and more obvious. The specific features of food as the material medium of symbols and signs, that are assimilated at the level of the most direct corporeal experience, determines its consumption as a complex system of communication links. Many processes in the sphere of gastronomic practices are cruel and global. For example, new nutritive horrors, change in the status of feast as permanent topos of human social and cultural identity reproduction. Gastronomic symbols are widely used in advertising as a tool of temptation intensively. Fast food is considered neutral from the perspective of national gastronomic cultures and therefore has become the foreground way gastronomic behavior. Moreover, modern gastronomic culture has produced the most actual today standard of thin body. The practice of fast food consumption has lead to market appearance of the new practices of gastronomic communication as well as the relationships between man and power and new gender order. It can be claimed that in the form of fast food (MAC-food) the symbolic content of food has overcome and absorbed its physical and technical aspects.